Health capital and economic performance in selected Southern African development Community (SADC) countries - Alungile Qoko; Kin Sibanda; Phakama Senzangakhona (Cogent Economics & Finance, 2024)
Understanding the relationship between health capital and economic performance is crucial for policymakers in Southern African Development Community (SADC) countries. This study explores this relationship in 14 SADC countries over a 14-year period (2005-2019), with GDP per capita as a measure of economic performance and health capital's impact analysed alongside labour force participation rate, institutional quality, and trade openness. To address potential outliers, the data was transformed using logarithms, and two panel unit root tests, Levin, Lien, and Chu (LLC), and Im, Pesaran, and Shin (IPS), were employed to test for stationarity of the series. The findings indicate a combination of integrated orders, including I(0) and I (1), but not I (2). Panel cointegration tests by Pedroni and Kao reveal cointegration, suggesting a long-run relationship between the variables. The study utilized the panel auto regressive distributed lag (ARDL) model with Pooled Mean Group analysis as the best estimator to investigate both long run and short run relationships. For robustness, the study employed the fully modified least squares (FMOLS) method and the fixed effects (FE) model. The empirical findings establish a significant and negative relationship between health capital and economic performance in the selected SADC countries. Based on these results, the study recommends that governments in the SADC region prioritize addressing issues related to leakages in the health sector to improve economic performance.
Keywords: 330; Economic performance; health capital; panelcointegration; panelautoregressive distributedlags; pooled mean group; southern african development community